Ixekizumab efficacy and safety in moderate‐to‐severe genital psoriasis. (1st October 2018) - Ryan, C.; Menter, A.; Guenther, L.; Blauvelt, A.; Bissonnette, R.; Meeuwis, K.; Sullivan, J.; Cather, J.C.; Yosipovitch, G.; Gottlieb, A.B.; Merola, J.F.; Callis Duffin, K.; et al.
Summary: Psoriasis is a common skin disease that affects about 2% of people worldwide. It presents with red, scaly, and often itchy patches that can affect skin anywhere on the body. About 63% of patients have psoriasis in the genital region at some point in the course of their disease. Genital psoriasis is difficult to treat and it can be a particularly painful, itchy, uncomfortable, and embarrassing form of psoriasis. It also leads to difficulties in personal relationships, sexual health, and overall quality of life. This study aimed to determine whether ixekizumab, a drug used to treat overall psoriasis, also successfully treats genital psoriasis. Patients with genital psoriasis from multiple global countries were treated with either ixekizumab or a placebo (a dummy injection lacking an active drug). The effect of ixekizumab was compared to placebo over 12 weeks of treatment using a combination of clinical tools to measure genital psoriasis severity as well as patient‐completed questionnaires about the impact of their genital psoriasis on their quality of life and sexual health. Ixekizumab provided greater improvements in genital psoriasis severity, with over 73% of patients having minimal or no genital psoriasis and 56% having no genital psoriasis at Week 12. The effect of ixekizumab was rapid, with clear improvements observed as early as the first week of treatment. Rapid and greater improvements were also seen in the severity of genital itching and the impact of genital psoriasis on the frequency of sexual activity. This study suggests that ixekizumab is an effective treatment for genital psoriasis.